Analisis Dampak Pelatihan Manajemen Risiko kepada Karyawan terhadap Jumlah Pelaporan Potensi Bahaya di PT. Alda Trans Papua - Titik Ekowati; Yuniar Istiyani (Jurnal Flight Attendant, 2025)
This study analyzes the impact of risk management training on hazard reporting behavior at PT. Alda Trans Papua, a high-risk aviation company. Hazard reporting is a critical indicator in the Safety Management System (SMS), yet the effectiveness of the training provided has never been evaluated in depth. Using a descriptive qualitative method through observation, semi-structured interviews with five training participants from various job levels (managers, supervisors, and staff), and documentation studies, this research aims to analyze the impact of training and identify factors influencing post-training reporting behavior. The findings indicate that risk management training positively increases employee awareness and proactive behavior in identifying and reporting potential hazards. Employees gain a better understanding of the importance of early risk identification as part of accident prevention. However, the implementation of reporting in the field still faces obstacles in the form of work practices that deviate from procedures (practical drift), external factors, and a poorly digitized reporting system. This research confirms that the success of reporting depends not only on training but also on three key factors: strong management commitment, an easily accessible reporting system, and a supportive safety culture (just culture). To maximize the impact of training, it is recommended to develop an integrated digital reporting system, enhance synergy between departments, and consistently apply the principles of just culture so that employees feel safe reporting without fear of blame. Future training should also be equipped with applicable visual examples through closer collaboration between the safety and operations teams.